2006
DOI: 10.1039/b514824c
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for internal structure in aqueous–organic nanodroplets

Abstract: The spatial distribution of species within an aerosol droplet influences how it interacts with its environment. Despite the ubiquity of multicomponent nanodroplets in natural and technological aerosols, there are no published measurements of their internal structure. Here, we report the first experimental results for structure in aqueous organic nanodroplets based on small angle neutron scattering by high number density aerosols. For H(2)O-n-butanol droplets, fitting of the diffraction patterns confirms the pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 18 publications
7
44
0
Order By: Relevance
“…Many organic compounds have very low solubilities in water, and, as a result, these mixtures display miscibility gaps separating water-rich and organic-rich phases within the droplet. [6][7][8] In particular, surface active components are likely to form films covering the droplets, [8][9][10] and indeed Tervahattu et al found evidence that fatty acids form a surface coating on marine aerosol particles. 11,12 Aqueousorganic aerosol droplets may also adopt radically different structures depending on their overall composition, on the solubility of organic compounds in the aqueous phase, and on the relative humidity.…”
Section: Introductionmentioning
confidence: 99%
“…Many organic compounds have very low solubilities in water, and, as a result, these mixtures display miscibility gaps separating water-rich and organic-rich phases within the droplet. [6][7][8] In particular, surface active components are likely to form films covering the droplets, [8][9][10] and indeed Tervahattu et al found evidence that fatty acids form a surface coating on marine aerosol particles. 11,12 Aqueousorganic aerosol droplets may also adopt radically different structures depending on their overall composition, on the solubility of organic compounds in the aqueous phase, and on the relative humidity.…”
Section: Introductionmentioning
confidence: 99%
“…One significant consequence of this difference is that rather than developing the core-shell structures favored by the amphiphilic compounds, 36 D 2 O-water nanodroplets favor a lens-on-sphere structure. 12,13 Thus, the higher condensation coefficients estimated here are consistent with a droplet structure that exposes at least some regions that favor water condensation.…”
Section: B Binary Nucleation and Condensationmentioning
confidence: 99%
“…The determination of the physical and optical properties of aerosols is necessary to further understand aerosol contribution to these effects. There is evidence to suggest that aerosols coated with a thin film of organic material are prevalent in the troposphere [2][3][4][5][6][7] . Mineral dust is a common source of solid aerosol 8,9 that is produced by wind action and can become coated with organic material such as lipids 9 arising from plant matter.…”
Section: Introductionmentioning
confidence: 99%